Clinical application of PARP inhibitors in ovarian cancer: from molecular mechanisms to the current status - Yongsong Wu; Shilin Xu; Shanshan Cheng; Jiani Yang; Yu Wang (BMC, 2023)
Abstract As a kind of gynecological tumor, ovarian cancer is not as common as cervical cancer and breast cancer, but its malignant degree is higher. Despite the increasingly mature treatment of ovarian cancer, the five-year survival rate of patients is still less than 50%. Based on the concept of synthetic lethality, poly (ADP- ribose) polymerase (PARP) inhibitors target tumor cells with defects in homologous recombination repair(HRR), the most significant being the target gene Breast cancer susceptibility genes(BRCA). PARP inhibitors capture PARP-1 protein at the site of DNA damage to destroy the original reaction, causing the accumulation of PARP-DNA nucleoprotein complexes, resulting in DNA double-strand breaks(DSBs) and cell death. PARP inhibitors have been approved for the treatment of ovarian cancer for several years and achieved good results. However, with the widespread use of PARP inhibitors, more and more attention has been paid to drug resistance and side effects. Therefore, further research is needed to understand the mechanism of PARP inhibitors, to be familiar with the adverse reactions of the drug, to explore the markers of its efficacy and prognosis, and to deal with its drug resistance. This review elaborates the use of PARP inhibitors in ovarian cancer.